2009
DOI: 10.1063/1.3247350
|View full text |Cite
|
Sign up to set email alerts
|

Accurate noise projection for reduced stochastic epidemic models

Abstract: We consider a stochastic susceptible-exposed-infected-recovered (SEIR) epidemiological model. Through the use of a normal form coordinate transform, we are able to analytically derive the stochastic center manifold along with the associated, reduced set of stochastic evolution equations. The transformation correctly projects both the dynamics and the noise onto the center manifold. Therefore, the solution of this reduced stochastic dynamical system yields excellent agreement, both in amplitude and phase, with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…For example, in a Susceptible-Exposed-Infected-Recovered (SEIR) epidemiological model, there are terms at low order in the normal form transform which cause a significant difference between the average stochastic center manifold and the deterministic manifold [21]. Therefore, when working with the SEIR model, one must use the stochastic normal form coordinate transform approach to obtain the correct projection of the noise onto the center manifold.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a Susceptible-Exposed-Infected-Recovered (SEIR) epidemiological model, there are terms at low order in the normal form transform which cause a significant difference between the average stochastic center manifold and the deterministic manifold [21]. Therefore, when working with the SEIR model, one must use the stochastic normal form coordinate transform approach to obtain the correct projection of the noise onto the center manifold.…”
Section: Discussionmentioning
confidence: 99%
“…And there is still an ongoing debate on generalizations to stochastic dynamical processes (see e.g. [10]). …”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper (Forgoston et al 2009), we showed how noise affects the timing of outbreaks for a time independent system. Therefore, it was concluded that it is essential to produce a low-dimensional system which captures the correct timing of the outbreaks as well as the amplitude and phase of any recurrent behavior for any given measured realization of an outbreak.…”
Section: Introductionmentioning
confidence: 98%